How Does Gender Quota Shape Gender Attitudes? - Yen-Chien Chen; Elliott Fan; Yu-Hsin Ho; Matthew Yi-Hsiu Lee; Jin-Tan Liu (Institute of Labor Economics (IZA), 2023)
Starting in 2002, each electoral district in Taiwan is required to reserve one seat for women out of every four seats at the local councils, creating a 'zigzag' function of female councilors proportion across districts. Using this function, we estimate the effects of exposure to female political leadership on gender attitudes and behaviors. For son preference, we find that the gender quota reduced the propensity for parents with two daughters to give a third-parity birth, whereas there is no such effect on parents with two children of other sex compositions. This finding is confirmed by the evidence of self-reported son preference revealed in survey data. We further find that the gender quota encouraged female high school graduates to attempt college admission and pursue a college major in law or political science, which commonly prepare students to develop a career in politics. The gender quota also empowers married women to play a more active role in multiple household decisions. Our findings support the hypothesis that female political leaders perform as role models who elicit more egalitarian gender attitudes from women.
Keywords: J16; J13; I23; D10; 330; gender quota; son preference; gender role model; gender norms